2016
DOI: 10.1515/sbe-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Life Expectancy: The Case of Iran

Abstract: Abstract:Regarding the link between economic growth and it`s public outcomes, this paper studies the effect of economic growth on life expectancy in Iran during 1966Iran during -2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
(22 reference statements)
6
8
0
Order By: Relevance
“…The higher growth rate makes family affluent; household head can spend more for the better health of family members including females. This finding is similar to those of Rahman and Alam [ 8 ], Rahman et al [ 9 ], Wang et al [ 25 ], Mahyar [ 35 ], and Shahbaz et al [ 36 ]. The urbanization rate has a positive effect on female life expectancy but an insignificant effect on the female adult mortality rate because of improved urban health facilities, access to information, better living standards, better employment resources and higher incomes for all people.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The higher growth rate makes family affluent; household head can spend more for the better health of family members including females. This finding is similar to those of Rahman and Alam [ 8 ], Rahman et al [ 9 ], Wang et al [ 25 ], Mahyar [ 35 ], and Shahbaz et al [ 36 ]. The urbanization rate has a positive effect on female life expectancy but an insignificant effect on the female adult mortality rate because of improved urban health facilities, access to information, better living standards, better employment resources and higher incomes for all people.…”
Section: Discussionsupporting
confidence: 91%
“…Wang et al [ 25 ] found that economic growth was positively linked with life expectancy in Pakistan by employing ARDL bounds test approach. Similar findings were also observed by Mahyar [ 35 ] for Iran, Ebenstein et al [ 37 ] for China, and Shahbaz et al [ 36 ] for 16 sub-Saharan African countries. Rahman et al [ 9 ] found that economic growth had a significant impact on increasing life expectancy and reducing the infant mortality rate but no significant impact on death rate in the case of 15 SAARC-ASEAN countries that employed fixed effects, random effects and GMM models.…”
Section: Literature Reviewsupporting
confidence: 87%
See 1 more Smart Citation
“…Azomahoo et al 8 , Husain 9 , Ecevit 10 , Ngangue and Manfred 11 have found positive relationship between LEB and economic growth and Cervellati and Sunde 12 have found positive relationship between LEB and economic growth after demographic transition analysing many countries together in their studies. Erdoğan and Bozkurt 13 , Akintunde et al 14 and Mahyar 15 , have found positive relationship between LEB and economic growth analysing a single country in their studies.…”
Section: Granger Causality Testsmentioning
confidence: 88%
“…Higher life expectancy facilitates rapid economic growth (Lorentzen et al, 2008). An individual who lives longer contributes to the progress of the economy (Mahyar, 2016). Increased productivity of available economic resources is built on the possibility of individual possessing higher life span.…”
Section: Introductionmentioning
confidence: 99%